Bronchiolitis obliterans syndrome associated with an immune checkpoint inhibitor in a patient with non-small cell lung cancer. (2023) - Takeda, Kenichiro; Miwa, Hideki; Kono, Masato; Hirama, Ryutaro; Oshima, Yuiko; Mochizuka, Yasutaka; Tsutsumi, Akari; Miki, Yoshihiro; Hashimoto, Dai; Nakamura, Hidenori
Abstract: A 75-year-old woman was admitted to our hospital with progressive dyspnea 7 months after second-line treatment with pembrolizumab for advanced non-small cell lung cancer. Chest radiography revealed hyperinflation in both lung fields, and pulmonary function tests revealed severe obstructive dysfunction without bronchodilator reversibility. There were no identifiable causes such as infections or autoimmune diseases. Therefore, bronchiolitis obliterans syndrome associated with immune checkpoint inhibitors was clinically diagnosed. Pembrolizumab was discontinued, but the respiratory dysfunction was irreversible and resulted in death. Bronchiolitis obliterans syndrome is an extremely rare but potentially severe adverse event associated with immune checkpoint inhibitor-related lung disease.